Molecular Mechanism of Caffeine in Preventing Bronchopulmonary Dysplasia in Premature Infants - Tian, Congliang; Li, Danni; Fu, Jianhua (Frontiers in Pediatrics, 2022)
Bronchopulmonary dysplasia (BPD) is a chronic respiratory complication commonly seen in premature infants. Following continuous advances in neonatal intensive care diagnosis and treatment technology, an increasing number of premature babies are being treated successfully. Despite these remarkable improvements, there has been no significant decline in the incidence of BPD; in fact, its incidence has increased as more extremely preterm infants survive. Therefore, in view of the impact of BPD on the physical and mental health of children and the increased familial and social burden on these children, early prevention of BPD is emphasized. In recent decades, the clinical application of caffeine in treating primary apnea in premature infants was shown not only to stimulate the respiratory center but also to confer obvious protection to the nervous and respiratory systems. Numerous clinical cross-sectional and longitudinal studies have shown that caffeine plays a significant role in the prevention and treatment of BPD, but there is a lack of overall understanding of its potential molecular mechanisms. In this review, we summarize the possible molecular mechanisms of caffeine in the prevention or treatment of BPD, aiming to better guide its clinical application.